Trauma patient transport times unchanged despite trauma center proliferation: A 10-year review. Issue 3 (10th March 2021) - Jones, Michael D.; Paulus, Jordan A.; Jacobs, Jordan V.; Bogert, James N.; Chapple, Kristina M.; Soe-Lin, Hahn; Weinberg, Jordan A.
Abstract : INTRODUCTION: In certain regions of the United States, there has been a dramatic proliferation of trauma centers. The goal of our study was to evaluate transport times during this period of trauma center proliferation. METHODS: Aggregated data summarizing level I trauma center admissions in Arizona between 2009 and 2018 were provided to our institution by the Arizona Department of Health Services. We evaluated patient demographics, transport times, and injury severity for both rural and urban injuries. RESULTS: Data included statistics summarizing 266, 605 level I trauma admissions in the state of Arizona. The number of state-designated trauma centers during this time increased from 14 to 47, with level I centers increasing from 8 to 13. Slight decreases in mean Injury Severity Score (rural, 9.4 vs. 8.4; urban, 7.9 vs. 7.0) were observed over this period. Median transport time for cases transported from the injury scene directly to a level I center remained stable in urban areas at 0.9 hours in both 2009 and 2018. In rural areas, transport times for these cases were approximately double but also stable, with median times of 1.8 and 1.9 hours. Transport times for cases requiring interfacility transfer before admission at a level I center increased by 0.3 hours for urban injuries (5.3–5.6 hours) and 0.9 hours for rural injuries (5.6–6.5 hours). CONCLUSION: Despite the threefold increase in the number of state-designated trauma centers, transport time has not decreased in urban or rural areas. This finding highlights the need for regulatory oversight regarding the number and geographic placement of state-designated trauma centers. LEVEL OF EVIDENCE: Care management, level IV, Epidemiological, level III.